СОЦІАЛЬНО-ЕКОНОМІЧНЕ СТАНОВИЩЕ МОЛОДІ: ПРОБЛЕМИ ПОЛІПШЕННЯ - Konischeva, N.I. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2009)
The article investigates the ways of improving the social and economic status of the youth due to activation of the state youth policy.